2019
DOI: 10.3389/fnins.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

10 Hz tACS Over Somatosensory Cortex Does Not Modulate Supra-Threshold Tactile Temporal Discrimination in Humans

Abstract: Perception of physical identical stimuli can differ over time depending on the brain state. One marker of this brain state can be neuronal oscillations in the alpha band (8–12 Hz). A previous study showed that the power of prestimulus alpha oscillations in the contralateral somatosensory area negatively correlate with the ability to temporally discriminate between two subsequent tactile suprathreshold stimuli. That is, with high alpha power subjects were impaired in discriminating two stimuli and more frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…Our first result demonstrating that tACS does not modulate STDT regardless of stimulation frequency is in line with previous evidence showing no effect of 10 Hz tACS applied over S1 on STDT 23 . Our finding that tACS did not affect overall near-threshold tactile stimuli perception contrasts with that of Sliva et al 21 , who showed a decreased performance in near-threshold stimuli perception during alpha tACS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our first result demonstrating that tACS does not modulate STDT regardless of stimulation frequency is in line with previous evidence showing no effect of 10 Hz tACS applied over S1 on STDT 23 . Our finding that tACS did not affect overall near-threshold tactile stimuli perception contrasts with that of Sliva et al 21 , who showed a decreased performance in near-threshold stimuli perception during alpha tACS.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we demonstrated that tACS failed to modify STDT and near-threshold tactile stimuli perception, not only when delivered at alpha frequency 22,23 , but even at beta and gamma frequencies. Moreover, our study showed that the phase of tACS stimulation over S1 did not affect near-threshold tactile stimuli perception.…”
Section: Discussionmentioning
confidence: 41%
“…In rabbits, motor behavioral effects (eyeblink) were induced at higher frequencies (30, 100 and 200 Hz) rather than 10 Hz (Márquez-Ruiz et al, 2016). Similarly, although tACS stimulation of the somatosensory cortex (SI) at alpha and high-gamma frequency was able to elicit tactile sensations (Feurra et al, 2011b), 10 Hz tACS did not modulate the ability to temporally discriminate between two subsequent tactile suprathreshold stimuli (Wittenberg et al, 2019). Overall, our data suggest that perturbations of neural oscillations can be beneficial for individuals with aberrant oscillations such as the elderly.…”
Section: Resultsmentioning
confidence: 97%
“…First, participants typically report sensations such as itching or tingling, but no rhythmic component (at least at common stimulation intensities, such as those applied here), and these sensations seem to diminish or disappear relatively quickly after stimulation onset (e.g., Antal et al, 2017;Kessler, Turkeltaub, Benson, & Hamilton, 2012). Second, participants do not seem to be able to reliably distinguish different tACS frequencies (Nakazono, Ogata, Kuroda, & Tobimatsu, 2016;Wittenberg, Morr, Schnitzler, & Lange, 2019), including those which produce stronger sensations (10 or 20 Hz) than the frequency applied in the current study (3.125 Hz). Kleinert, Szymanski, & Müller (2017) also reported that participants are unable to determine whether frontal and parietal regions were stimulated in-or out-of-phase from each other.…”
Section: Limitations and Future Directionsmentioning
confidence: 85%